Perbandingan Konsentrasi ZPT (BAP dan NAA) Pada Media MS Terhadap Pertumbuhan Kalus Eksplan Daun Muda Tanaman Karet (Hevea brasiliensis Muell. Arg) - Sukamto, Dwi Sucianingtyas; Maharani, Lila; Lestari, Inget Puji (Fakultas MIPA UNM, 2017)
Abstract. Rubber is known in Indonesia since the Dutch colonial period. Indonesia is the second largest natural rubber producer in the world after Thailand, rubber production contributes greatly to the Indonesian economy. Propagation of rubber seedlings to date is still done by grafting is by using the eyes of buds and seed plants, one of the alternatives to meet the demand for rubber seedlings that are increasing and not dependent on the season and to produce the clonal rootstock is homogeneous by tissue culture techniques. This study aims to find out the response of callus formation of young leaf rubber plant leaves (Hevea brasiliensis Muell, Arg) on MS medium with different concentration of ZPT (BAP and NAA). This research uses Cross Sectional type of observation research, with combination of MS and ZPT media used ie MS with BAP 1.5 ppm + NAA 0,05 ppm, BAP 2 ppm + NAA 0,1 ppm, BAP 2.5 ppm + NAA 0.2 ppm. The parameters observed were the forming of callus, callus texture and callus color for 21 days. Based on the results of the study showed that MS treatment with ZPT concentration (BAP 1.5 ppm + NAA 0.05ppm) gave the best result for callus formation response with highest explanation percentage of 0,06%.Keywords. Calli, Concentration ZPT, Hevea brasiliensis Muell.Arg.Â